LEGO Star wars character encyclopedia - Dolan, Hannah; Dowsett, Elizabeth; Hibbert, Clare 1970-; Last, Shari; Taylor, Victoria (Children's author); DK Publishing, Inc (New York DK Publishing, 2015)
Presents the Lego action figures based on the "Star Wars" universe, detailing the number of pieces and describing each figure and its variations, when they were made, the playsets in which they appear, and the movie to which they relate
Episode I -- Episode II -- Clone wars -- Episode III -- Rebels -- Episode IV -- Episode V -- Episode VI -- Legends
At head of title: LEGO Star wars
Includes index
1
Keywords: LEGO toys -- Juvenile literature; Models and modelmaking -- Juvenile literature; Star Wars figures -- Juvenile literature; Star Wars films -- Juvenile literature; LEGO toys; Models and modelmaking; Star Wars figures; Star Wars films